Fake antimalarials in Southeast Asia are a major impediment to malaria control: multinational cross-sectional survey on the prevalence of fake antimalarials. - Dondorp, A; Newton, P; Mayxay, M; Van Damme, W; Smithuis, F; Yeung, S; Petit, A; Lynam, A; Johnson, A; Hien, T; Mcgready, R; Farrar, J; et al. (2004)
OBJECTIVE: To assess the prevalence of counterfeit antimalarial drugs in Southeast (SE) Asia. DESIGN: Cross-sectional survey. SETTING: Pharmacies and shops selling antimalarial drugs in Myanmar (Burma), Lao PDR, Vietnam, Cambodia and Thailand. MAIN OUTCOME MEASURES: Proportion of artemisinin derivatives or mefloquine containing drugs of substandard quality. RESULTS: Of the 188 tablet packs purchased which were labelled as 'artesunate' 53% did not contain any artesunate. All counterfeit artesunate tablets were labelled as manufactured by 'Guilin Pharma', and refinements of the fake blisterpacks made them often hard to distinguish from their genuine counterparts. No other artemisinin derivatives were found to be counterfeited. Of the 44 mefloquine samples, 9% contained <10% of the expected amount of active ingredient. CONCLUSIONS: An alarmingly high proportion of antimalarial drugs bought in pharmacies and shops in mainland SE Asia are counterfeit, and the problem has increased significantly compared with our previous survey in 1999-2000. This is a serious threat to public health in the region.